Économie de plateforme et droit social : enjeux prospectifs et approche juridique comparative - Isabelle Daugareilh; Christophe Degryse; Philippe Pochet (European Trade Union Institute (ETUI), 2019)
– This Working Paper brings together two parallel but complementary approaches to the impact of the platform economy on working conditions and social law. The first part of the study shows that the business models of some platforms is a combination of technological disruption and social evasion. The second part of this working paper confirms that it is in the gaps and ambiguities in social legislation that platforms are trying to legitimise a business model abrogating all social responsibility. It is in this sense that we can talk about the risk of "social evasion" of several major platforms, exactly in the same way as fiscal evasion.
Keywords: 330; digital services; business model; Working conditions; social law; Digitale Dienste; Geschäftsmodell; Arbeitsbedingungen; Sozialrecht